2020
DOI: 10.1038/s41467-020-15658-2
|View full text |Cite|
|
Sign up to set email alerts
|

The morphology, molecular development and ecological function of pseudonectaries on Nigella damascena (Ranunculaceae) petals

Abstract: Pseudonectaries, or false nectaries, the glistening structures that resemble nectaries or nectar droplets but do not secrete nectar, show considerable diversity and play important roles in plant-animal interactions. The morphological nature, optical features, molecular underpinnings and ecological functions of pseudonectaries, however, remain largely unclear. Here, we show that pseudonectaries of Nigella damascena (Ranunculaceae) are tiny, regional protrusions covered by tightly arranged, non-secretory polygon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…N. damascena, commonly known as love-in-a-mist or devil-in-the-bush, is native to the Mediterranean region and West Asia, but today is grown as an ornamental plant in temperate regions of Europe (Fico et al 2000;Jabbour et al 2015). The entomophilous flowers consist of usually blue petaloid sepals lying on lacy bracts and long-stalked petals located at the base of the stamens (Zhao et al 2011;Liao et al 2020). The seeds of N. damascena are produced in bloated capsules that partially open on the dorsal and ventral suture (Zohary 1983).…”
Section: Introductionmentioning
confidence: 99%
“…N. damascena, commonly known as love-in-a-mist or devil-in-the-bush, is native to the Mediterranean region and West Asia, but today is grown as an ornamental plant in temperate regions of Europe (Fico et al 2000;Jabbour et al 2015). The entomophilous flowers consist of usually blue petaloid sepals lying on lacy bracts and long-stalked petals located at the base of the stamens (Zhao et al 2011;Liao et al 2020). The seeds of N. damascena are produced in bloated capsules that partially open on the dorsal and ventral suture (Zohary 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, because ectopic expression of polarity genes can sometimes lead to regional outgrowths (Fukushima and Hasebe, 2014), we propose that the polarity genes NidaKAN1 (peaked at S7) and NidaYAB5 (peaked at S8/9) are required for the formation of pseudonectaries. Consistent with this notion, a recent study has demonstrated that knockdown of NidaYAB5 can indeed led to the complete loss of pseudonectaries (Liao et al, 2020).…”
Section: Candidate Genes Associated With Morphological Charactersmentioning
confidence: 56%
“…Presumably, it was the reactivation of the KNOXI and CUC genes that led to the formation of the upper lip. Nevertheless, we still cannot exclude the possibility that expression rearrangement of adaxial/abaxial genes also contributed considerably to this process, because the abaxial gene NidaYAB5 is also expressed in the adaxial side of the upper lip (Yao et al, 2019;Liao et al, 2020). More studies are needed to elucidate the exact roles of these genes.…”
Section: Mechanisms Underlying Marginal and Ventral Elaborationmentioning
confidence: 99%
See 2 more Smart Citations